ChemInform Abstract: A Base‐Mediated Mild Sulfenylation of Indoles and Pyrrole with α‐Acylthiones. Issue 13 (March 2015) - Viglianisi, Caterina; Marcantoni, Enrico; Carapacchi, Vanessa; Menichetti, Stefano; Marsili, Laura
Abstract Indole derivatives react with 1 equiv.